2017
DOI: 10.1134/s0006297917100029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms of sporadic Alzheimer’s disease: Studies on rodent models in vivo

Abstract: In this review, recent data are presented on molecular and cellular mechanisms of pathogenesis of the most widespread (about 95%) sporadic forms of Alzheimer's disease obtained on in vivo rodent models. Although none of the available models can fully reproduce the human disease, several key molecular mechanisms (such as dysfunction of neurotransmitter systems, especially of the acetylcholinergic system, β-amyloid toxicity, oxidative stress, neuroinflammation, mitochondrial dysfunction, disturbances in neurotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…injections of streptozotocin (STZ) [47,118], subcutaneous (s.c.) injections of D-galactose [78,119], i.p. injections of MK-801 (a non-competitive NMDA receptor antagonist) [120], olfactory bulbectomy (OBE) [121] and i.c.v. injections of lipopolysaccharide (LPS) [116,[122][123][124] or colchicine [116].…”
Section: Experimental Models Of Admentioning
confidence: 99%
“…injections of streptozotocin (STZ) [47,118], subcutaneous (s.c.) injections of D-galactose [78,119], i.p. injections of MK-801 (a non-competitive NMDA receptor antagonist) [120], olfactory bulbectomy (OBE) [121] and i.c.v. injections of lipopolysaccharide (LPS) [116,[122][123][124] or colchicine [116].…”
Section: Experimental Models Of Admentioning
confidence: 99%
“…Oxidative stress is considered a key factor in the AD pathogenesis [28]. Aβ is responsible for promoting the generation of ROS, the oxidation of lipids to destabilize the neuronal membrane, and decreasing the activity of antioxidant enzymes such as SOD and catalase, which encourage the necrosis and apoptosis states [29]. Reports indicate that Aβ 25–35 interacts with the cell membrane, altering the structure and function of the lipid bilayer and augmenting the concentration of ROS and lipid peroxidation, as shown in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that Aβ 25–35 promotes an inflammatory response mediated by the production of proinflammatory cytokines, which could trigger the generation of ROS and the proliferation of glial cells, leading to reactive gliosis [43]. All these mechanisms of neurodegeneration cause damage to the structure and function of the limbic system, particularly in the Hp, a brain region that has a key role in the development of spatial memory, in such a way that a characteristic of the neurotoxicity of Aβ 25–35 is the deterioration in learning and spatial memory, which is supported by a large number of publications [17,18,24,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Modeling of cholinergic dysfunction allows to reproduce memory impairments, which are among the central symptoms of AD associated dementia. Several neurotoxic substances were used in order to produce loss of BFCN in animals [99]. Till the mid of 1990 s, ethylcholine aziridinium ion (AF64A) was widely used for this purpose, the toxin with a structure similar to that of choline.…”
Section: Alzheimer's Diseasementioning
confidence: 99%